2013
DOI: 10.1074/jbc.m113.495465
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Interleukin-1β in Neuropathic Rats Enhances Glutamate Release from the Primary Afferents in the Spinal Dorsal Horn through Coupling with Presynaptic N-Methyl-d-aspartic Acid Receptors*

Abstract: Background: Excessive activation of glutamate receptors is crucial to the genesis of neuropathic pain. Results: Endogenous IL-1␤ in neuropathic rats enhances glutamate release by increasing presynaptic NMDA receptor activities via sphingomyelinase signaling. Conclusion: Coupling between IL-1␤ receptors and presynaptic NMDA receptors contributes to the genesis of neuropathic pain. Significance: Interruption of such coupling could be an effective approach for the treatment of neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 78 publications
4
109
0
Order By: Relevance
“…57 TNF-α and IL-1β can increase excitatory glutamatergic synaptic activities in the SDH. 27,58 We recently demonstrated that endogenous IL-1β in neuropathic animals increases presynaptic glutamate release from nociceptive primary afferents through coupling with presynaptic NMDA receptors. 27,31 Furthermore, postsynaptic AMPA receptors activities are also enhanced by endogenous IL-1β in neuropathic animals through the MyD88 signaling pathway at postsynaptic neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…57 TNF-α and IL-1β can increase excitatory glutamatergic synaptic activities in the SDH. 27,58 We recently demonstrated that endogenous IL-1β in neuropathic animals increases presynaptic glutamate release from nociceptive primary afferents through coupling with presynaptic NMDA receptors. 27,31 Furthermore, postsynaptic AMPA receptors activities are also enhanced by endogenous IL-1β in neuropathic animals through the MyD88 signaling pathway at postsynaptic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…27,58 We recently demonstrated that endogenous IL-1β in neuropathic animals increases presynaptic glutamate release from nociceptive primary afferents through coupling with presynaptic NMDA receptors. 27,31 Furthermore, postsynaptic AMPA receptors activities are also enhanced by endogenous IL-1β in neuropathic animals through the MyD88 signaling pathway at postsynaptic neurons. 27 Thus, it is conceivable that through increasing the activation of glial cells and production of IL-1β, suppression of AMPK activities leads to enhanced activation of neurons in the SDH and induces hypersensitivity in animal nociceptive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…When glial PRRs are activated, it leads to a positive feedback loop of neuroinflammation through the release of proinflammatory mediators, such as TNFα, IL-1β, IL-6, prostaglandins (PGs), interferon γ (IFNγ), brain-derived neurotrophic factor (BDNF) and ROS (Adami et al, 2004;Carpentier et al, 2005;Coull et al, 2005;Gorina et al, 2011;Hanisch, 2002;Pedrazzi et al, 2006;Ponath et al, 2007;Raghavendra et al, 2004). Pre-and post-synaptic terminals of nociceptive neurons express receptors for these proinflammatory factors and the intracellular signalling that follows their activation leads to increased membrane excitability and enhanced synaptic transmission (Gao et al, 2007;Nishio et al, 2013;Park et al, 2011;Stellwagen et al, 2005;Stellwagen and Malenka, 2006;Viviani et al, 2003;Yan and Weng, 2013;Zhao et al, 2007) (see details in Fig. 3).…”
Section: Involvement Of Glial Cells In Central Sensitizationmentioning
confidence: 99%
“…The reason for this difference is unknown, but may be related to the duration of administration of morphine. Functional coupling between IL-1b receptors and presynaptic NMDA receptors in terminals of primary afferents is dependent on N-SMase and could be an important factor in response of dorsal horn neurons during neuropathic pain [193]. The expression of microglial-specific molecules Iba-1 and CD11b is increased in the spinal cord during neuropathic pain induced by partial sciatic nerve ligation, and intrathecal injection of an inhibitor of N-SMase, GW4869, or an inhibitor of ceramide biosynthesis, fumonisin B1 reduces microglial activation and tactile allodynia [194].…”
Section: Painmentioning
confidence: 99%